Formaldehyde content of milk: 1. Cows fed on protein concentrates treated with different amounts of formaldehyde - Syrjälä-Qvist, Liisa; Setälä, Jouko (Agricultural and Food Science, 1982)
The formaldehyde content was determined on the milk of four dairy cows fed on protein concentrates treated with increasing amounts of formaldehyde 1)0, 2) 0.8, 3)2.4 and 4)4.0 g HCHO/100 g crude protein. The experiment was arranged according to a 4X4 Latin square design and each test period lasted 10 days. The average milk yield of the cows during the experiment was 9.4kg/day. The protein concentrate was a mixture of soybean meal, skimmed-milk powder, meat-bone meal, brewer’s grains, molasses, molassed beat pulp and urea, and the basic feeds were hay, straw and barley. The HCHO-treated protein constituted 42-50 % of the total crude protein of the diet. The daily amounts of formaldehyde received by the cows on the different diets were: 1)0g, 2)2.9 g, 3) 5.1 g and 4) 14.6g, and the formaldehyde contents per kg of milk were, respectively, 1)0.2 mg, 2)0.3 mg, 3) 0.6 mg and 4) 1.7 mg. Thus the milk samples contained formaldehyde even when the protein had not been treated. Of the formaldehyde added to the feeds, only 0.06-0.07 % was found in the milk. The formaldehyde content of the milk reached a constant level within the first two days of the test period.